2016
DOI: 10.5194/amt-9-2207-2016
|View full text |Cite
|
Sign up to set email alerts
|

A review of sources of systematic errors and uncertainties in observations and simulations at 183 GHz

Abstract: Abstract. Several recent studies have observed systematic differences between measurements in the 183.31 GHz water vapor line by space-borne sounders and calculations using radiative transfer models, with inputs from either radiosondes (radiosonde observations, RAOBs) or short-range forecasts by numerical weather prediction (NWP) models. This paper discusses all the relevant categories of observation-based or model-based data, quantifies their uncertainties and separates biases that could be common to all caus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 67 publications
(65 reference statements)
4
31
0
Order By: Relevance
“…However, Bobryshev et al () show that carefully matching radiosonde profiles with satellite observations (e.g., using only radiosonde profiles with less than 15 km horizontal drift) and also using cloud masks from visible satellite instruments can potentially reduce the differences between the simulated and observed Tbs. However, the biases shown for water vapor channels in Figure as well as in other studies, for example, Bobryshev et al () and Brogniez et al (), are still considerably larger than the biases shown in Figure for the temperature sounding channels.…”
Section: Double Difference Techniquesupporting
confidence: 44%
“…However, Bobryshev et al () show that carefully matching radiosonde profiles with satellite observations (e.g., using only radiosonde profiles with less than 15 km horizontal drift) and also using cloud masks from visible satellite instruments can potentially reduce the differences between the simulated and observed Tbs. However, the biases shown for water vapor channels in Figure as well as in other studies, for example, Bobryshev et al () and Brogniez et al (), are still considerably larger than the biases shown in Figure for the temperature sounding channels.…”
Section: Double Difference Techniquesupporting
confidence: 44%
“…These were reduced by almost an order of magnitude via amplitude ratioing with the calibration tone [Kursinski et al, 2016]. Residual amplitude scintillations may be the largest source of random error in the least square fits.…”
Section: Sources Of Uncertainty and Validation Of Resultsmentioning
confidence: 99%
“…These results support the prediction that an ATOMMS system in LEO would be a major advance toward achieving the fundamental satellite observing system goals of very high vertical 25 resolution, all-weather temperature and water vapor sounding with very small random and absolute uncertainties, across the entire globe in support of weather prediction, climate monitoring and the quantitative constraints on process needed to improve models. A mission design concept using a constellation of very small ATOMMS satellites using cubesat technology is given in Kursinski et al, 2016. ATOMMS has the potential to provide global observations from space that approach, and in some ways exceed, the performance of sondes.…”
Section: Discussionmentioning
confidence: 99%
“…SAPHIR channels in the 183 GHz band are capable of probing the atmospheric humidity from the surface to the tropopause. However, some research studies have shown a discrepancy between observed and radiative transfer model‐simulated brightness temperatures in the 183 GHz band, with increasing differences towards the wings of the line (Brogniez et al, ; Kursinski et al, ). Hence, assimilation of channel 6 of SAPHIR using the radiative transfer model RTTOV‐9 (Saunders, ) used in present study may result in an error in the vertical extent of the layers which this channel influences.…”
Section: Saphir: Instrument Detailsmentioning
confidence: 99%